1997
DOI: 10.1002/(sici)1096-8628(19971128)73:1<10::aid-ajmg3>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal atresia with distal tracheoesophageal fistula in a patient with fronto-metaphyseal dysplasia

Abstract: Fronto-metaphyseal dysplasia (FMD) is an uncommon but clinically striking condition affecting bone and connective tissue. The terms used to define this syndrome fail to cover all the reported findings, the abnormalities not being confined to the metaphyses and to the frontal bones. We report on a patient who, in addition to the clinical manifestations characteristic of the syndrome, showed esophageal atresia with distal tracheoesophageal fistula. Particular emphasis is given to the extraskeletal manifestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Long segment tracheal stenosis, however, was observed in neither of the two chromosomal conditions. Interestingly, airway obstruction may occur in the same syndromal disorder as esophageal atresia and tracheo‐esophageal fistula as, e.g., in familial frontometaphyseal dysplasia [Fitzsimmons et al, 1982; Franceschini et al, 1997]. Reviewing the literature on dup 12p and del 4q, we found that the same is true for the 4q‐syndrome.…”
Section: Discussionsupporting
confidence: 53%
“…Long segment tracheal stenosis, however, was observed in neither of the two chromosomal conditions. Interestingly, airway obstruction may occur in the same syndromal disorder as esophageal atresia and tracheo‐esophageal fistula as, e.g., in familial frontometaphyseal dysplasia [Fitzsimmons et al, 1982; Franceschini et al, 1997]. Reviewing the literature on dup 12p and del 4q, we found that the same is true for the 4q‐syndrome.…”
Section: Discussionsupporting
confidence: 53%
“…Familial cases raised the possibility of an X‐linked trait [Beighton and Hamersma, 1980; Gorlin and Winter, 1980], or an autosomal dominant inheritance with variable expression [Weiss et al, 1976]. The association of upper airway malformations and recurrent respiratory symptoms have been emphasized by Franceschini et al [1997]. Mental retardation is uncommon in FMD [Reardon et al, 1991].…”
Section: Introductionmentioning
confidence: 99%
“…Ethical approval for this study was obtained from the Otago Ethics Committee. To obtain a consistent set of diagnostic criteria for the diagnosis of FMD, all reports of male patients previously diagnosed with the condition and described in sufficient detail were evaluated and phenotypic characteristics tabulated [Gorlin and Cohen, 1969; Holt et al, 1972; Danks and Mayne, 1974; Sauvegrain et al, 1975; Weiss et al, 1975, 1976; Kassner et al, 1976; Medlar and Crawford, 1978; Sellars and Beighton, 1978; Kanemura et al, 1979; Ullrich et al, 1979; Beighton and Hamersma, 1980; Fitzsimmons et al, 1982; Jend‐Rossmann et al, 1984; Leggett, 1988; Glass and Rosenbaum, 1995; Nishimura et al, 1995; Ehrenstein et al, 1997; Franceschini et al, 1997; Kung and Sloan, 1998; Boduroglu and Tuncbilek, 1999; Vinay et al, 2000; Morava et al, 2003; Zenker et al, 2004; Stefanova et al, 2005] (Tables I and II). Characteristics were divided into mandatory, major and minor features on account of their frequency and specificity for the disorder.…”
Section: Methodsmentioning
confidence: 99%